The Role of Big Data Analytics, Digital Capability, and Agility on Firm Competitiveness in Indonesia - Mardani Eka Ningrum; Nurul Ulya; Imran Iskandar; Muhammad Nur Arafah (Journal Management & Economics Review (JUMPER), 2026)
In this study, the impact of Big Data Analytics, Digital Capability, and Organizational Agility on Firm Competitiveness in Indonesia was analyzed. Being a part of the rapidly developing digital era, it becomes necessary for organizations to apply data-driven approaches, improve their digital competencies and develop agility to ensure competitiveness. A quantitative research design was used in the study. A cross-sectional survey involving 220 responses from managers and professionals was used in this case. The data obtained in the process of the survey were analyzed using the Structural Equation Modeling (SEM). It can be stated that each of Big Data Analytics, Digital Capability, and Organizational Agility impacts Firm Competitiveness positively and significantly. However, Digital Capability is the most influential variable. Organizational Agility has more impact on Firm Competitiveness than Big Data Analytics. Thus, the studied variables explain 68.3% of variance of Firm Competitiveness. Therefore, it can be stated that Firm Competitiveness in the digital era is determined by the application of technologies and organizational agility.